Syndecan-1 Controls Lung Tumorigenesis by Regulating miRNAs Packaged in Exosomes - Parimon, Tanyalak (Am J Pathol, 2018)
Syndecan-1 is a transmembrane proteoglycan expressed prominently by lung epithelium and has pleiotropic functions such as regulating cell migration, proliferation, and survival. Loss of syndecan-1 expression by lung cancer cells is associated with higher-grade cancers and worse clinical prognosis. We evaluated the effects of syndecan-1 in various cell-based and animal models of lung cancer and found that lung tumorigenesis was moderated by syndecan-1. We also demonstrate that syndecan-1 (or lack thereof) alters the miRNA cargo carried within exosomes exported from lung cancer cells. Analysis of the changes in miRNA expression identified a distinct shift toward augmented procancer signaling consistent with the changes found in lung adenocarcinoma. Collectively, our work identifies syndecan-1 as an important factor in lung cancer cells that shapes the tumor microenvironment through alterations in miRNA packaging within exosomes.